Nosology and classification of genetic skeletal disorders: 2015 revision. (23rd September 2015) - Bonafe, Luisa; Cormier‐Daire, Valerie; Hall, Christine; Lachman, Ralph; Mortier, Geert; Mundlos, Stefan; Nishimura, Gen; Sangiorgi, Luca; Savarirayan, Ravi; Sillence, David; Spranger, Jürgen; Superti‐Furga, Andrea; et al.
Abstract : The purpose of the nosology is to serve as a "master" list of the genetic disorders of the skeleton to facilitate diagnosis and to help delineate variant or newly recognized conditions. This is the 9th edition of the nosology and in comparison with its predecessor there are fewer conditions but many new genes. In previous editions, diagnoses that were phenotypically indistinguishable but genetically heterogenous were listed separately but we felt this was an unnecessary distinction. Thus the overall number of disorders has decreased from 456 to 436 but the number of groups has increased to 42 and the number of genes to 364. The nosology may become increasingly important today and tomorrow in the era of big data when the question for the geneticist is often whether a mutation identified by next generation sequencing technology in a particular gene can explain the clinical and radiological phenotype of their patient. This can be particularly difficult to answer conclusively in the prenatal setting. Personalized medicine emphasizes the importance of tailoring diagnosis and therapy to the individual but for our patients with rare skeletal disorders, the importance of tapping into a resource where genetic data can be centralized and made available should not be forgotten or underestimated. The nosology can also serve as a reference for the creation of locus‐specific databases that are expected to help in delineating genotype–phenotype correlations and to harbor the information that will be gained by combining clinical observations and next generation sequencing results. © 2015 Wiley Periodicals, Inc.